The Impact of Visiting Nature Tourism on Tourists’ Mental Health and Revisit Intentions - Meidina Shafa Auditania Alfian; Ahmad Hudaiby Gakih Kusumah (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
Mental health has become an important issue in today’s society, and many people are looking for ways to restore it. One common option is visiting nature tourism, as natural environments are believed to provide peace and reduce stress. This study aims to analyze the impact of visiting nature tourism on mental health and how improved mental health influences revisit intention. The research used a quantitative approach with data collected from 253 respondents who had visited Taman Hutan Raya Ir. Djuanda. The data were analyzed using SmartPLS 4.0 to examine the relationships among variables. The results show that visits to nature tourism significantly improve tourists’ mental health, where the natural atmosphere helps to reduce stress and anxiety. Improved mental health also has a significant effect on revisit intention. Different from previous studies, this research highlights not only the effect of nature tourism on mental health but also how the improvement in mental health motivates tourists to return. These findings suggest that nature tourism managers should maintain the natural environment, provide relaxation facilities, and promote the positive benefits of nature tourism for mental health.